Strategi Preventif dan Represif Pembiayaan Bermasalah untuk Konsistensi Kesehatan Bank (Studi Kasus BSI KC Bojonegoro) - Yuria, Ima Yuriani; Setia Rini Arista (Jurnal Perbankan Syariah, 2024)
This research discusses preventive and repressive strategies in dealing with problematic financing so that the level of bank health that has been achieved is well maintained. Based on facts in the field, financing problems often occur among customers, especially at the Bank Syariah Indonesia Bojonegoro Branch Office. Therefore, the aim of this research is to find out more about the handling of problematic financing, both from preventive and repressive strategies carried out by BSI KC Bojonegoro, the factors that trigger problematic financing at BSI KC Bojonegoro, as well as the mechanisms implemented by BSI KC. Bojonegoro in overcoming financing problems. The method used in this research is a qualitative descriptive method using field research. The results of the research state that there are 2 strategies for handling problematic financing carried out by BSI KC Bojonegoro, namely preventive and repressive strategies. Preventive strategies include providing information regarding the legal consequences of breach of contract, then evaluating the management of the financing distribution portfolio, and evaluating the financing unit. Then repressive strategies include contacting customers, visiting customers' homes, giving warning letters, deliberation, rescheduling, reconditioning, restructuring, writing off, auction selling collateral, and finally taking legal action. Then there are 2 factors that cause financing problems, namely internal and external factors. It is hoped that this research can provide new insights regarding handling problematic financing to readers and can be used as evaluation material for BSI KC Bojonegoro.